(untitled) (Research, Society and Development, 2021)
Vaccination of the population against Covid-19 is essential, as is knowledge of the epidemiological characteristics and distribution of doses applied. The objective is to characterize the distribution of the number of applied doses of vaccines against Covid-19 and to outline the profile of those vaccinated in the Lower Amazon Region (RBA). Descriptive, quantitative study referring to the number of applied doses of vaccines notified in the RBA. Of the doses sent to the population, 80% of these were administered. The age group with the highest number of 1st dose applied is 18 to 59 years old, there was a reduction in the 2nd dose applied. in relation to the first dose; the most stable age group in terms of first and second dose vaccination coverage is the age group of 60 years or more. The group that showed greater adherence to the vaccine were health professionals; pregnant women had a lower percentage of equivalence between the estimated population, between doses. The North had the worst vaccination coverage rates among population/doses applied, in the RBA there were large indices of disparity when taking into account the previous relationship. It was difficult to find complete and up-to-date data on the doses applied and the populations covered by the Covid–19 vaccines. The files were encrypted by programs that were difficult for laypeople to access, a fact that contributed to a better analysis. The disparity between the number of doses sent and the number of doses administered highlighted the need for active search measures and dissemination of more accurate information about the population’s vaccination.